Development of a software system for monitoring of home based rehabilitation - Celetaria, Charmaine Elaiza Alimboyoguen (2018)
Singapore has the highest smartphone adoption rate in the world at 85%. Countries in Asia are using smartphones to get access online instead of computers [1]. As advanced technology develops, more people depend on smartphone for their daily lives. People tend to use their phone in various tasks with the help of mobile applications, which are out in the market. The purpose of developing a software system for monitoring of home-based rehabilitation is to assists doctors, caregivers and family members when facilitating aftercare at home.